Remarkable Photocatalytic and Antimicrobial Activities of Iron Oxide Nanoparticles Synthesized through Green Route Using Citrus maxima Peel Extract - Sapkota, Kamal Prasad; Das, Bijay Kumar; Sharma, Motee Lal (Molung Educational Frontier, 2025)
The present research work reports the successful synthesis of the iron oxide nanoparticles (IONPs) through green route, their characterization and their application for their antimicrobial and photocatalytic performance. The IONPs were prepared using Citrus maxima peel extract through green synthesis method. The peel extract was found to contain important phytochemicals such as polyphenols, flavonoids, and terpenoids, which facilitate the reduction of metal precursors and stabilize metal nanoparticles. This approach offers scalability, simplicity, and non-toxicity, making it a notable strategy in green nanotechnology for producing nanoparticles. The as-synthesized nanoparticles were applied for the antimicrobial and photocatalytic performance. It was found that the as-synthesized IONPs were excellent photocatalysts for the degradation of methylene blue solution with 98.13% degradation within the recorded time of 90 minutes in the presence of natural sunlight. Moreover, the IONPs demonstrated good anti-bacterial activity against Bacillus subtilis and E. coli and good anti-fungal activity against Candida albicans.